Genomic and phenotypic characterization of a Clostridioides difficile strain of the epidemic ST37 type from China - Li, Chunhui; Heuler, Joshua; Zhu, Duolong; Meng, Xiujuan; Chakraborty, Soumyadeep; Harmanus, Céline; Wang, Shaohui; Peng, Zhong; Smits, Wiep Klaas; Wu, Anhua; Sun, Xingmin (Frontiers in Cellular and Infection Microbiology, 2024)
Clostridioides difficile strains of sequence type (ST) 37, primarily including PCR ribotype (RT) 017, are prevalent in mainland China. Our study aimed to compare the major virulence factors of an epidemic C. difficile isolate of ST37 type (Xy06) from China with the well-characterized C. difficile reference strains R20291 (RT027) and CD630E (ST54), as well as a Chinese ST54 strain (Xy07) isolated from the same hospital. The Xy06 genome was predicted to harbor two complete prophages and several transposon-like elements. Comparative analysis of PaLoc revealed a truncated tcdA gene, a functional tcdB gene, a functional tcdC gene, and well-conserved tcdR and tcdE genes. Phenotypic comparisons showed that Xy06 was a robust producer of TcdB, readily sporulated and germinated, and strongly bound to human gut epithelial cells. In a mouse model of C. difficile infection, Xy06 was more virulent than strains CD630E and Xy07 and was comparable to strain R20291 in virulence. Our data suggest the potential threat of the epidemic ST37 strains in China.